1995
DOI: 10.1111/j.1445-5994.1995.tb01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the home management of non‐fatal acute myocardial infarction in Perth, Western Australia between 1984 and 1993

Abstract: The management at home of cases of non-fatal AMI in people of working age in Perth has remained at a negligible level from 1984 to 1993. Thus a register based on admissions to hospital for AMI will accurately reflect trends in AMI in people of working age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Limitations. The WADLS captures atherothrombotic events treated in hospital only and we will have missed a proportion of events that were diagnosed and treated in primary care, 33 possibly leading to conservative estimates of incidence and prevalence. In particular, our PAD population may be underestimated relative to CHD and CeVD due to greater propensity to treat lower severity PAD in a community setting.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Limitations. The WADLS captures atherothrombotic events treated in hospital only and we will have missed a proportion of events that were diagnosed and treated in primary care, 33 possibly leading to conservative estimates of incidence and prevalence. In particular, our PAD population may be underestimated relative to CHD and CeVD due to greater propensity to treat lower severity PAD in a community setting.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…9 Our methods did not capture silent MIs or ACS events treated out of hospital. A previous study has shown that a negligible proportion of patients (Ͻ1%) with recognized nonfatal MI in Perth are treated completely in primary care, 40 and there is no evidence to suggest that this has increased. The exclusion of ACS patients who were treated in or died in an emergency department is unlikely to bias our findings because a high proportion of patients who undergo troponin testing are admitted to the hospital, and Յ1% die in the emergency department before admission.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The safety of early discharge was demonstrated by the very low 6-month mortality rate (0.8%). Despite this initial report, safety concern of such an approach still remains, 1 as it has only been applied to a minority of patients.…”
Section: Risk Stratification and Early Discharge After Primary Angiopmentioning
confidence: 99%
“…1,2 Increasing economic pressures have intensified the need for risk scores to tailor in-hospital treatment of patients with STEMI according to their risk of future events. 3 Identification of a low-risk subset of patients seems to be an attractive way to reduce hospitalization and costs.…”
mentioning
confidence: 99%